Out of programme experience: going away to bring something back: closing the loop. Issue 2 (2nd November 2012) - Valliani, Talal
Abstract : In the January 2011 edition of Frontline Gastroenterology, I was the lead author of an article: Out of programme experience and training: going away to bring something back. 1 Since then, I have taken time out of my speciality training programme—an out of programme experience. I thought it would be of interest to trainees to read about how I organised my out of programme experience and how this time away has helped me to develop my unique selling point.